Development of an aerogel-based thermal coating for the energy retrofit and the prevention of condensation risk in existing buildings. (21st October 2019) - Fantucci, Stefano; Fenoglio, Elisa; Grosso, Giulia; Serra, Valentina; Perino, Marco; Marino, Valentina; Dutto, Marco
Abstract : The energy retrofit of existing buildings, particularly historic and/or listed buildings, presents several issues; that is, the compatibility between the identified solutions and the heritage value or the internal space reduction (if internal interventions have to be adopted). For this reason, an emerging method to address the target of the energy retrofit of historic buildings is the use of advanced materials characterized by high thermal insulation performance. In the framework of a European research project (Horizon 2020), a novel aerogel-based insulating coating, particularly suitable for the mitigation of thermal bridges and for the prevention of the condensation risk, is under development. In this article, both the laboratory and in-field research activities are described. The first was aimed at optimizing the thermohygrometric properties of the coating; the latter dealt with the results of a monitoring activity carried out on a full-scale application. Results highlight that the internal application of 12 mm of the developed material can lead to a significant increase in indoor surface temperature (about 1.4 °C) with a decrease in the wall U-value of about 27%. Moreover, a mitigation of the thermal bridges was observed with an increase in the minimum surface temperature up to 1.6 °C.